Structural features and biological activities of the polysaccharides from Astragalus membranaceus - Jin, Mingliang; Zhao, Ke; Huang, Qingsheng; Shang, Peng (International journal of biological macromolecules, 2014)
Recently, a great deal of interest has been developed to isolate and investigate novel bioactive components with health benefit effects from natural resources. The dried root of Astragalus membranaceus, one of the most popular health-promoting herbal medicines, has been used historically as an immunomodulating agent for the treatment of common cold, diarrhea, fatigue and anorexia for more than 2000 years. Modern phytochemistry and pharmacological experiments have proved that polysaccharide is one of the major active ingredients in the root of A. membranaceus with various important bioactivities, such as immunomodulation, antioxidant, antitumor, anti-diabetes, antiviral, hepatoprotection, anti-inflammation, anti-atherosclerosis, hematopoiesis and neuroprotection. The aim of the present review is to summarize previous and current references and give a comprehensive summary regarding the structural features and biological activities of A. membranaceus polysaccharides in order to provide new insight for further development of these macromolecules.